Media Fun Thinkers Based on Calistug Questions - Jummita Jummita; I Gusti Ayu Tri Agustiana; I Ketut Dibia (Indonesian Journal Of Educational Research and Review, 2021)
Continuous use of gadgets can hurt students. This has an impact on behaviour patterns and student learning activities. The need for balancing media in online learning is media that is concrete. This type of research is development research using the ADDIE procedure. The test subjects in this study were 2 subject matter experts, 2 learning media experts, 2 practitioners and 7 students. The method used to collect data in this study is the questionnaire. The data collection instrument used in this study was a rating scale. The data analysis technique used in this research is descriptive qualitative and quantitative data analysis. The results of the study are the results of the assessment given by subject matter experts assessing 4.63 (very good), learning media experts giving an assessment of 4.82 (very good), the assessment given by practitioner response experts is 4.85 (very good), and the results of the media student response test were 4.95 (very good). So media fun thinkers based on calistung questions can be used in the learning process. The assessment implies that this learning media can be used by teachers and in the learning process.